Composite resin color stability: influence of light sources and immersion media - Patricia Aleixo dos Santos Domingos; Patrícia Petromilli Nordi Sasso Garcia; Ana Luisa Botta Martins de Oliveira; Regina Guenka Palma-Dibb (University of São Paulo, 2011)
OBJECTIVE: This study evaluated the influence of light sources and immersion media on the color stability of a nanofilled composite resin. MATERIAL AND METHODS: Conventional halogen, high-power-density halogen and high-power-density light-emitting diode (LED) units were used. There were 4 immersion media: coffee, tea, Coke® and artificial saliva. A total of 180 specimens (10 mm x 2 mm) were prepared, immersed in artificial saliva for 24 h at 37±1ºC, and had their initial color measured with a spectrophotometer according to the CIELab system. Then, the specimens were immersed in the 4 media during 60 days. Data from the color change and luminosity were collected and subjected to statistical analysis by the Kruskall-Wallis test (p<0.05). For immersion time, the data were subjected to two-way ANOVA test and Fisher's test (p<0.05). RESULTS: High-power-density LED (ΔE=1.91) promoted similar color stability of the composite resin to that of the tested halogen curing units (Jet Lite 4000 plus - ΔE=2.05; XL 3000 - ΔE=2.28). Coffee (ΔE=8.40; ΔL=-5.21) showed the highest influence on color stability of the studied composite resin. CONCLUSION: There was no significant difference in color stability regardless of the light sources, and coffee was the immersion medium that promoted the highest color changes on the tested composite resin.